Control-oriented modeling and adaptive backstepping control for a nonminimum phase hypersonic vehicle. (September 2017) - Ye, Linqi; Zong, Qun; Tian, Bailing; Zhang, Xiuyun; Wang, Fang
Abstract: In this paper, the nonminimum phase problem of a flexible hypersonic vehicle is investigated. The main challenge of nonminimum phase is the prevention of dynamic inversion methods to nonlinear control design. To solve this problem, we make research on the relationship between nonminimum phase and backstepping control, finding that a stable nonlinear controller can be obtained by changing the control loop on the basis of backstepping control. By extending the control loop to cover the internal dynamics in it, the internal states are directly controlled by the inputs and simultaneously serve as virtual control for the external states, making it possible to guarantee output tracking as well as internal stability. Then, based on the extended control loop, a simplified control-oriented model is developed to enable the applicability of adaptive backstepping method. It simplifies the design process and releases some limitations caused by direct use of the no simplified control-oriented model. Next, under proper assumptions, asymptotic stability is proved for constant commands, while bounded stability is proved for varying commands. The proposed method is compared with approximate backstepping control and dynamic surface control and is shown to have superior tracking accuracy as well as robustness from the simulation results. This paper may also provide a beneficial guidance for control design of other complex systems. Highlights: The extended control loop principle is developed to design a stable nonlinear controller through backstepping for nonminimum phase hypersonic vehicle, which guarantees the stability of the both internal states and external states. The nonminimum phase problem of hypersonic vehicle is dealt with by model simplification and adaptive backstepping. This work may provide a beneficial guidance for control design of other complex systems. We adopt a strategic way to proceed with the stability proof. Asymptotic stability is proved for constant commands while bounded stability is proved for varying commands.